Genome Sequence of Deep-Sea Manganese-Oxidizing Bacterium Marinobacter manganoxydans MnI7-9 - Wang, Haifang (American Society for Microbiology, 2012)
Here we report the draft genome of Marinobacter manganoxydans MnI7-9, isolated from a deep-sea hydrothermal vent in the Indian Ocean and capable of oxidizing manganese even when there is a very high concentration of Mn(2+). The strain also displayed high resistance and adsorption ability toward many metal(loid)s.